2022
DOI: 10.5194/essd-14-795-2022
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of a daily gridded snow water equivalent product for the land region above 45° N based on a ridge regression machine learning approach

Abstract: Abstract. The snow water equivalent (SWE) is an important parameter of surface hydrological and climate systems, and it has a profound impact on Arctic amplification and climate change. However, there are great differences among existing SWE products. In the land region above 45∘ N, the existing SWE products are associated with a limited time span and limited spatial coverage, and the spatial resolution is coarse, which greatly limits the application of SWE data in cryosphere change and climate change studies.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…We assess below-normal winter snow storage using ERA5-Land reanalysis snow water equivalent (SWE) data . Shao et al (2022) found that these data performed better than other published gridded snow data products, and we also found that this dataset provided a much better match to snow survey data (Vionnet et al, 2021), than a Canadian data product (Environment and Climate Change Canada, 2021). 𝑆𝑊𝐸 𝑚𝑎𝑥 is the maximum catchment-averaged SWE for each year.…”
Section: Climate and Anthropogenic Driverssupporting
confidence: 50%
“…We assess below-normal winter snow storage using ERA5-Land reanalysis snow water equivalent (SWE) data . Shao et al (2022) found that these data performed better than other published gridded snow data products, and we also found that this dataset provided a much better match to snow survey data (Vionnet et al, 2021), than a Canadian data product (Environment and Climate Change Canada, 2021). 𝑆𝑊𝐸 𝑚𝑎𝑥 is the maximum catchment-averaged SWE for each year.…”
Section: Climate and Anthropogenic Driverssupporting
confidence: 50%
“…In this study, we used the state-of-the-art ERA5-Land data set, which is featured with flexible spatial and temporal resolution (Muñoz-Sabater et al, 2021) and good performance in identifying extreme temperature events (Sheridan et al, 2020). More importantly, the SWE of ERA5-Land agrees better with station observations compared with other datasets (Shao et al, 2022), making it an ideal data set to characterize snow droughts. To further demonstrate the robustness of our results, we compared the CSDHW events detected based on ERA5-Land with those by chance (You & Wang, 2021).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…ERA5‐Land generally outperforms ERA5 over the US, while ERA5 performs better over Europe. It is noteworthy that the ERA5‐Land SWE has good performance for heights ranging between ∼1,500 and ∼3,000 m (Muñoz‐Sabater et al., 2021) and the best performance in the elevation interval of 300–400 m (Shao et al., 2022) but it is also known to have too large SWE sum estimates over the mountainous regions.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate our model results, we use the latest land component of the reanalysis product ERA5-Land produced by the European Center for Medium-Range Weather Forecasts as a reference. This product is an enhanced global data set for ERA5 (Muñoz-Sabater, 2019; Muñoz-Sabater et al, 2021), which has been found to perform well in the evaluation of nine gridded Northern Hemisphere snow SWE products as part of the European Space Agency Satellite Snow Product Intercomparison and Evaluation Exercise (SnowPEx) across a range of snow conditions (Mortimer et al, 2020;Shao et al, 2022). Although Mortimer et al (2020) did not explicitly endorse any single product, they did note that ERA5 is one of the products that perform best across the range of snow conditions captured by the validation data set.…”
Section: Benchmark Gridded Sswei From Era5-landmentioning
confidence: 99%